الإطار القانوني لاندماج الشركات: دراسة مقارنة - السراج، إيهاب عبدالمجيد محمد إسماعيل (كلية دلتا العلوم والتكنولوجيا, 2022)
تناولت الدراسة الاندماج بنوعيه باعتباره الوسيلة التي تحقق أقصى درجة من درجات التركز الاقتصادي، ويجري إعداد مشروع الاندماج في ضوء ما أسفرت عنه المباحثات الأولية، ويتم عرض المشروع بعد اعتماده من مجالس إدارة الشركات الداخلة في الاندماج على الجمعيات العامة غير العادية للشركات الداخلة في الاندماج لاتخاذ قرار بشأنه، وتنتج عن عملية الاندماج آثار عديدة ومهمة تطال الشركات الداخلة فيه، كما تطال الشركاء أو المساهمين في هذه الشركات، وتمتد آثار الاندماج إلى دائني هذه الشركات، وللاندماج آثار على العقود التي أبرمتها الشركة أو الشركات المندمجة، وله كذلك تداعياته على قواعد المنافسة المشروعة في النشاط الاقتصادي، وتنبع أهمية الدراسة من اتجاه الاقتصاد المعاصر بما يشهده من تطور ومنافسة تجارية محتدمة نحو التركز بهدف الوصول إلى أفضل النتائج، وقد هدفت الدراسة إلى تناول الجوانب القانونية للاندماج في القانون السوداني والقانون المصري وكذلك النظام السعودي. تمثلت مشكلة الدراسة في حل المشاكل والصعوبات التي تعترض الشركات التجارية في حال اندماجها، وكيفية التعامل معها، والالتزامات السابقة أو المصاحبة أو اللاحقة للاندماج، وقد قام البحث على المنهج الوصفي التحليلي المقارن مع التشريع المصري والسعودي. وقد توصلت الدراسة إلى نتائج وتوصيات، ومن أهم النتائج أن انتقال ذمة الشركة المندمجة إلى الشركة الدامجة أو الجديدة يعد من أبرز خصائص الاندماج التي تميزه عن غيره من الأنظمة المشابهة، ومن أبرز التوصيات التي توصلت إليها الدراسة ضرورة تدخل المشرع بالنص على حقوق دائني الشركة المندمجة، وتقرير حقهم في الاعتراض على الاندماج، وطلب ضمانات في مواجهة الشركة الدامجة. The study covered the merger as the method that achieves the maximum degree of economic concentration. The merger project is being prepared as it the results of the initial discussions. The project after its approval by the boards of directors of the companies entering into the merger, is presented to the extraordinary general assemblies of the companies entering into the merger to take a decision regarding it. The merger process results in many important effects that affect the companies involved in it, as well as the partners or shareholders in these companies, and the effects of the merger extend to the creditors of these companies, and the merger has implications for the contracts concluded by the company or the merged companies as well as its repercussions on the rules of legitimate competition in economic activity. The importance of the study comes from the trend of the contemporary economy with its development and intense commercial competition towards concentration in order to reach the best results. The study aimed to cover the legal aspects of the mergein the Sudanese law and the Egyptian law as well as the Saudi system The problem of the study consisted in researching solving the problems and difficulties encountered by commercial companies in the event of their merger, how to deal with them, and the obligations prior, accompanying or subsequent to the merger. the research was based on the descriptive analytical approach compared with the Egyptian and Saudi legislation. The study reached conclusions and recommendations. Among the most important results is that the transfer of the merging company’s liability to the merging or new company is one of the most prominent merger characteristics that distinguish it from other similar systems. Among the most prominent recommendations reached by the study is the necessity for the legislator to intervene by stipulating the rights of the merging company’s creditors, to decide their right to object to the merger, and to request guarantees in the face of the merging company.
Keywords: الشركات الاقتصادية -- التنمية المستدامة -- القوانين والتشريعات -- الشركات التجارية